Composite negative pole piece, battery and electric equipment
By designing a composite structure of nanosheet-shaped silicon active material and graphite active layer in the negative electrode sheet of lithium-ion battery, the powdering problem caused by volume expansion of silicon active material during lithium storage is solved, and the cycle stability of the electrode is significantly improved.
Patent Information
- Application Number
- CN202411673364.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-21
AI Technical Summary
As the negative electrode material of lithium-ion batteries, the volume expansion of silicon exceeds 300% during lithium storage, resulting in powdering problems and the shedding of active materials, reducing the cyclic stability of the electrode.
A composite negative electrode sheet is designed, including a current collector, a first active layer and a second active layer. The silicon active material in the first active layer is in the shape of a nanosheet, distributed in the active material housing pores in the current collector, and the second active layer is composed of graphite, covering the first active layer to prevent the volume expansion of the silicon active material.
Through this structural design, the cyclic stability of the composite negative electrode sheet is significantly improved, the strain during the charge and discharge process is reduced, and the powdering and shedding problem of silicon active material is reduced.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a composite negative electrode sheet, a battery and an electrical device. Background Art
[0002] Due to the rapid development and widespread application of portable electronic devices and electric vehicles, there is an urgent need for lithium-ion batteries with high specific energy and long cycle life. Currently, commercial lithium-ion batteries mainly use graphite as the negative electrode material. However, since the theoretical specific capacity of graphite is only 372mAh / g, the further improvement of the specific energy of lithium-ion batteries is limited.
[0003] Silicon has a very high lithium insertion capacity (up to 4200mAh / g) and a low lithium storage potential, and is an ideal new lithium storage material, which has attracted widespread attention from researchers. However, the volume expansion of silicon during lithium storage exceeds 300%, which is prone to pulverization and causes the active material to fall off from the current collector, greatly reducing the cycle stability of the electrode. Summary of the invention
[0004] Based on this, it is necessary to provide a composite negative electrode sheet that can effectively inhibit the pulverization and shedding of silicon active materials in order to address the problems in the above-mentioned background technology, and the composite negative electrode sheet has significantly higher cycle stability.
[0005] According to some embodiments of the present disclosure, a composite negative electrode sheet is provided, comprising:
[0006] A current collector, the current collector having a plurality of active material containing holes opening on the surface of the current collector and having bottoms located in the current collector;
[0007] a first active layer, wherein the active material in the first active layer includes a silicon active material, the silicon active material is in the form of nanosheets, the first active layer is disposed in contact with the surface of the current collector, and at least a portion of the silicon active material is located in the active material containing hole; and
[0008] The second active layer comprises graphite, is disposed on a side of the first active layer away from the current collector, and entirely covers the first active layer.
[0009] In some embodiments of the present disclosure, the ratio of the thickness of the first active layer to the thickness of the second active layer is 1:(0.2~1.5).
[0010] In some embodiments of the present disclosure, the depth of the active material containing hole is 3 μm to 9 μm, and the overall thickness of the first active layer is 15 μm to 50 μm.
[0011] In some embodiments of the present disclosure, in the current collector, the diameter of the active material containing hole is 20 μm to 100 μm; and / or,
[0012] The openings of all the active material containing holes on the surface of the current collector account for 30% to 80% of the surface of the current collector.
[0013] In some embodiments of the present disclosure, in the first active layer, the thickness of the silicon active material is 5 nm to 100 nm; and / or,
[0014] The radial size of the silicon active material is 100nm-2000nm.
[0015] In some embodiments of the present disclosure, the active material in the first active layer further includes a carbon active material, and the carbon active material is selected from one or more of graphite, hard carbon, soft carbon and graphene, and in the first active layer, the mass ratio of the silicon active material to the carbon active material is 1:(0.5-2); and / or,
[0016] The active material in the first active layer accounts for more than 80% by mass of the first active layer.
[0017] In some embodiments of the present disclosure, the first active layer further includes at least one of a first conductive agent and a first adhesive; wherein,
[0018] The first conductive agent is selected from one or more of conductive carbon black, carbon nanotubes, graphene, carbon nanofibers and carbon-coated tin nanowires.
[0019] In some embodiments of the present disclosure, the mass proportion of graphite in the second active layer is greater than 90%, and the second active layer further includes at least one of a second conductive agent and a second binder.
[0020] Furthermore, the present disclosure also provides a battery, which includes a negative electrode sheet, a positive electrode sheet and an electrolyte; the positive electrode sheet and the negative electrode sheet are arranged opposite to each other, and the negative electrode sheet is a composite negative electrode sheet as described in any of the above embodiments.
[0021] Furthermore, the present disclosure also provides an electrical device, which includes an electrical main body and a battery as described in any of the above embodiments.
[0022] The composite negative electrode sheet disclosed in the present invention includes a current collector, a first active layer and a second active layer. An active material accommodating hole is provided in the current collector, and the first active layer contains a silicon active material in the form of nanosheets. The active material accommodating hole can accommodate the nanosheet-shaped silicon active material and form a good electrical contact with the silicon active material to provide a better ability to conduct electrons. More importantly, the nanosheet-shaped silicon active material is sparsely distributed in the active material accommodating hole. Therefore, there are more vacancies in the active material accommodating hole and abundant space can be reserved for the volume change of the silicon active material. At the same time, the graphite material in the second active layer can inhibit the upward expansion of the silicon active material. The above two factors work together to reduce the strain of the composite negative electrode sheet as a whole during the charge and discharge process, thereby significantly improving the problem of pulverization and shedding of the silicon active material. Experiments have shown that compared with other sheets that do not have the above structure, the composite negative electrode sheet has significantly higher cycle stability. DETAILED DESCRIPTION
[0023] The following is a detailed description of the embodiments of the technical solution of the present application. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the description and claims of this application and any variations thereof are intended to cover non-exclusive inclusions.
[0025] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0026] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0027] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0028] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0029] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0030] The present disclosure provides a composite negative electrode plate, which includes: a current collector, the current collector having a plurality of active material containing holes opening on the current collector surface and the bottom of which is located in the current collector. A first active layer, the active material in the first active layer includes a silicon active material, the silicon active material is in the form of nanosheets, the first active layer is contacted and arranged on the surface of the current collector, and at least part of the silicon active material is located in the active material containing holes. And, a second active layer, the second active layer includes graphite, the second active layer is arranged on the side of the first active layer away from the current collector, and the second active layer covers the first active layer as a whole.
[0031] The composite negative electrode plate of the present disclosure is arranged based on the following technical concept: when filled in the pores of the current collector, the nano-sheet silicon active material is sparsely distributed in the pores, which means that there are more vacancies in the pores of the current collector and can reserve abundant space for the volume change of the silicon active material. On this basis, the graphite in the second active layer arranged above is in a lamellar structure, which can block the volume expansion of the silicon active material toward the top. Therefore, during the charge and discharge process, the silicon active material mainly expands toward the inside of the pores of the current collector, and the overall strain of the first active layer and the second active layer located above the current collector is also relatively small, thereby significantly improving the problem of pulverization and shedding of the silicon active material. Experiments have shown that compared with other pole pieces that do not have the above structure, the composite negative electrode plate has significantly higher cycle stability.
[0032] In this embodiment, the composite negative electrode plate includes a current collector, a first active layer and a second active layer. The current collector has a plurality of active material receiving holes opening on the current collector surface and the bottom of which is located in the current collector. The active material in the first active layer includes a silicon active material, which is in the form of nanosheets. The first active layer is contacted and arranged on the surface of the current collector, and at least part of the silicon active material is located in the active material receiving hole. The second active layer includes graphite, and the second active layer is arranged on the side of the first active layer away from the current collector, and the second active layer covers the first active layer as a whole.
[0033] As an example of this embodiment, the material of the current collector is a conductive material. Further, the material of the current collector is a metal, for example, the material of the current collector may include one or more of copper, aluminum, iron and silver.
[0034] As an example of this embodiment, the ratio of the thickness of the first active layer to the thickness of the second active layer is 1:(0.2-1.5). The second active layer designed with this ratio has a strong blocking and inhibitory effect on the first active layer, which can further improve the cycle capacity retention rate of the negative electrode sheet.
[0035] As a further example of this embodiment, the ratio of the thickness of the first active layer to the thickness of the second active layer can be 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, or the ratio of the thickness of the first active layer to the thickness of the second active layer can also be between any two of the above ratios.
[0036] As an example of this embodiment, part of the first active layer can be disposed in the active material receiving hole, and another part of the first active layer can be disposed above the current collector, that is, the bottom end of the first active layer can be located in the active material receiving hole, and the top end of the first active layer can be higher than the opening of the active material receiving hole. The active material receiving hole can provide a certain expansion space during the volume expansion process of the silicon active material.
[0037] As an example of this embodiment, the depth of the active material accommodating hole is 3μm~9μm, and the overall thickness of the first active layer is 15μm~50μm. The volume expansion of the first active layer of this thickness during the charge and discharge process is relatively limited. The depth design of the active material accommodating hole can provide a relatively sufficient accommodating space for the silicon active material in the first active layer. It can be understood that the overall thickness of the first active layer refers to the height difference between the top of the first active layer and the bottom of the first active layer.
[0038] As a further example of this embodiment, the depth of the active material containing hole may be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, or 9 μm, or the depth of the active material containing hole may be between any two of the above depths.
[0039] As an example of this embodiment, the ratio of the depth of the active material containing hole to the thickness of the current collector is (1-3):4.
[0040] As a further example of this embodiment, the overall thickness of the first active layer may be 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, or 50 μm, or the overall thickness of the first active layer may be between any two of the above thicknesses.
[0041] As an example of this embodiment, the diameter of the active material accommodating hole is 20 μm to 100 μm. The active material accommodating hole in this diameter range can provide sufficient space for the expansion of the silicon active material.
[0042] As a further example of this embodiment, the pore size of the active material containing hole may be 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 50 μm, 60 μm, 80 μm, or 100 μm, or the pore size of the active material containing hole may be between any two of the above pore sizes.
[0043] As an example of this embodiment, the cross-sectional shape of the active material containing hole may be a regular shape or an irregular shape, wherein the regular shape may be a triangle, a square, a rectangle, a circle, an ellipse, a rhombus or a regular pentagon.
[0044] As an example of this embodiment, the openings of all active material containing holes on the surface of the current collector account for 30% to 80% of the surface of the current collector.
[0045] As a further example of this embodiment, the openings of all active material containing holes on the surface of the current collector occupy 30%, 40%, 50%, 60%, 70%, 80% of the surface of the current collector, or may be between any two of the above proportions.
[0046] As an example of this embodiment, in the first active layer, the thickness of the silicon active material is 5 nm to 100 nm. Further, the thickness of the silicon active material is 5 nm, 10 nm, 20 nm, 30 nm, 40 nm, 50 nm, 60 nm, 80 nm, 100 nm, or the thickness of the silicon active material may also be between any two of the above thicknesses.
[0047] As an example of this embodiment, in the first active layer, the radial dimension of the silicon active material is 100 nm to 2000 nm. Further, the radial dimension of the silicon active material is 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 700 nm, 1000 nm, 1500 nm, 2000 nm, or the radial dimension of the silicon active material may also be between any two of the above dimensions.
[0048] As an example of this embodiment, the silicon active material is selected from one or more of silicon, silicon monoxide, and silicon alloys. Further, the silicon active material may include one or more of silicon nanosheets, silicon monoxide nanosheets, and silicon alloy nanosheets.
[0049] As an example of this embodiment, the active material in the first active layer further includes a carbon active material, and the carbon active material is selected from one or more of graphite, hard carbon, soft carbon and graphene. It can be understood that the silicon active material and the carbon active material can be present in the first active layer in a mixed manner.
[0050] As a further example of this embodiment, in the first active layer, the mass ratio of the silicon active material to the carbon active material is 1:(0.5-2). For example, the mass ratio of the silicon active material to the carbon active material can be 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:1, 1:1.2, 1:1.4, 1:1.6, 1:1.8, 1:2, or the mass ratio of the silicon active material to the carbon active material can be between any two of the above mass ratios.
[0051] As an example of this embodiment, the mass proportion of the active material in the first active layer is more than 80%. For example, the mass proportion of the active material in the first active layer can be 80%, 82%, 85%, 88%, 90%, 92%, 95%, 98%, or the mass proportion of the active material in the first active layer can be between any two of the above mass proportions. It can be understood that in this embodiment, the active material includes a silicon active material, and the active material can also include a carbon active material.
[0052] As an example of this embodiment, the first active layer further includes at least one of a first conductive agent and a first binder.
[0053] As a further example of this embodiment, the first conductive agent is selected from one or more of conductive carbon black, carbon nanotubes, graphene, carbon nanofibers, and carbon-coated tin nanowires. In this embodiment, the first conductive agent includes carbon nanotubes and carbon-coated tin nanowires.
[0054] As a further example of this embodiment, the first binder may be selected from one or more of polyvinyl pyrrolidone, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, carboxymethyl cellulose, and a copolymer of styrene and butadiene.
[0055] As a further example of this embodiment, the first active layer further includes a first dispersant. The first dispersant may be selected from sodium carboxymethyl cellulose.
[0056] As an example of this embodiment, the mass proportion of graphite in the second active layer is more than 90%. It can be understood that the graphite in the second active layer can not only be used to suppress the upward expansion of the silicon active material, but also can be used as an active material participating in the charge and discharge process.
[0057] As an example of this embodiment, the graphite may be selected from flake graphite.
[0058] As a further example of this embodiment, the mass proportion of graphite in the second active layer may be 90%, 92%, 95%, or 98%, or the mass proportion of graphite in the second active layer may be between any two of the above mass proportions.
[0059] As a further example of this embodiment, the second active layer further includes at least one of a second conductive agent and a second binder.
[0060] As a further example of this embodiment, the second conductive agent may be selected from one or more of conductive carbon black, carbon nanotubes, graphene, and carbon nanofibers.
[0061] As a further example of this embodiment, the second binder may be selected from one or more of polyvinyl pyrrolidone, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, carboxymethyl cellulose, and a copolymer of styrene and butadiene.
[0062] As a further example of this embodiment, the second active layer further includes a second dispersant. The second dispersant may be selected from sodium carboxymethyl cellulose.
[0063] The present disclosure also provides a method for preparing the above-mentioned composite negative electrode sheet, which comprises the following steps.
[0064] Step S1, coating a first slurry containing a silicon active material on a current collector.
[0065] In this embodiment, the current collector has a plurality of active material containing holes which are opened on the surface of the current collector and have their bottoms located in the current collector.
[0066] In this embodiment, the silicon active material is in the form of nanosheets. It is understood that during the coating process, due to the limited flowability of the slurry and the structural characteristics of the nanosheets themselves, it is difficult for the nanosheet-shaped silicon active material to be fully filled in the active material accommodating holes of the current collector, so that there is space in the active material accommodating holes to accommodate the volume expansion of silicon.
[0067] As an example of this embodiment, the active material in the first slurry further includes a carbon active material, and the carbon active material is selected from one or more of graphite, hard carbon, soft carbon and graphene.
[0068] As an example of this embodiment, the first slurry further contains at least one of a first conductive agent and a first binder. The first conductive agent is selected from one or more of conductive carbon black, carbon nanotubes, graphene, carbon nanofibers, and carbon-coated tin nanowires. In this embodiment, the first conductive agent includes carbon nanotubes and carbon-coated tin nanowires. The first binder can be selected from one or more of polyvinyl pyrrolidone, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, carboxymethyl cellulose, and a copolymer of styrene and butadiene.
[0069] As an example of this embodiment, the first slurry further includes a first dispersant. The first dispersant may be selected from sodium carboxymethyl cellulose.
[0070] As an example of this embodiment, the solid content in the first slurry is 40% to 49%. For example, the solid content in the first slurry can be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, or the solid content in the first slurry can also be between any two of the above ratios.
[0071] As an example of this embodiment, the viscosity of the first slurry may be 2000 mPa·s to 6000 mPa·s.
[0072] Step S2, coating a second slurry containing graphite on the current collector.
[0073] As an example of this embodiment, the second slurry further contains at least one of a second conductive agent and a second binder. The second conductive agent is selected from one or more of conductive carbon black, carbon nanotubes, graphene and carbon nanofibers. The second binder can be selected from one or more of polyvinyl pyrrolidone, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, carboxymethyl cellulose and a copolymer of styrene and butadiene.
[0074] As an example of this embodiment, the second slurry further includes a second dispersant. The second dispersant may be selected from sodium carboxymethyl cellulose.
[0075] As an example of this embodiment, the solid content in the second slurry is 40% to 49%. For example, the solid content in the second slurry can be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, or the solid content in the second slurry can also be between any two of the above ratios.
[0076] As an example of this embodiment, the viscosity of the second slurry may be 2000 mPa·s to 6000 mPa·s.
[0077] As an example of this embodiment, after coating the first slurry and the second slurry on the first active layer, it also includes: drying the current collector coated with the first slurry and the second slurry to remove the solvent in the first slurry and the second slurry, and forming the first active layer and the second active layer respectively.
[0078] It can be understood that the thickness of the first active layer and the second active layer can be controlled by controlling the amount of the coated first slurry and the second slurry, respectively.
[0079] Through the above steps S1 to S2, a composite negative electrode sheet as in the above embodiment can be prepared.
[0080] On the other hand, the present disclosure further provides a battery, which includes a positive electrode sheet and a negative electrode sheet, the positive electrode sheet and the negative electrode sheet are arranged opposite to each other, and the negative electrode sheet includes the negative electrode sheet as described in any of the above embodiments.
[0081] As an example of this embodiment, the positive electrode sheet includes a positive electrode current collector and a positive electrode active layer.
[0082] As an example of this embodiment, the positive electrode active layer includes a positive electrode active material selected from one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, layered ternary positive electrode materials, spinel lithium nickel manganese oxide, lithium iron phosphate, lithium iron manganese phosphate, lithium manganese phosphate and lithium cobalt phosphate.
[0083] In this embodiment, the battery may be a lithium-ion battery.
[0084] Furthermore, the present disclosure also provides an electrical device, which includes a functional body and a battery as described in the above embodiment, and the battery is used to supply energy to the functional body.
[0085] As some examples of this embodiment, the power-consuming device may be a mobile phone, a laptop computer, a smart watch, or an electric car.
[0086] The present application is further described in detail below in conjunction with several specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0087] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0088] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.
[0089] Example 1
[0090] A porous copper foil with a thickness of 12 μm is used as the current collector, wherein the hole depth is about 6 μm and the hole diameter is about 35 μm.
[0091] Silicon nanosheets, carbon-coated tin nanowires, conductive carbon black, single-walled carbon nanotubes, styrene-butadiene rubber (binder) and sodium carboxymethyl cellulose (dispersant) are mixed in a mass ratio of 90:5:0.5:0.5:2:2, and an appropriate amount of deionized water is added. The first slurry is prepared according to a suitable homogenization process under the action of a vacuum mixer, wherein the solid content is about 45% and the viscosity is 4000 mPa·s.
[0092] Graphite, conductive carbon black, styrene-butadiene rubber and sodium carboxymethyl cellulose were mixed in a mass ratio of 97.5:0.5:1.5:0.5, and an appropriate amount of deionized water was added. The second slurry was prepared according to a suitable homogenization process under the action of a vacuum mixer, wherein the solid content was about 45% and the viscosity was 4000 mPa·s.
[0093] The first slurry and the second slurry are sequentially coated on the surface of the porous copper foil using a double-layer coating machine and dried to form a first active layer and a second active layer, respectively. The first active layer has a thickness of 30 μm, and the second active layer has a thickness of 10 μm.
[0094] Example 2
[0095] The main difference between Example 2 and Example 1 is the first slurry, whose raw material ratio is as follows: silicon dioxide nanosheets, conductive agent (90% conductive carbon black and 10% single-walled carbon nanotubes), styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed in a mass ratio of 97.5:0.5:2:0.5.
[0096] Example 3
[0097] The main difference between Example 3 and Example 1 lies in the first slurry, whose raw material ratio is as follows: first, graphite and silicon dioxide nanosheets are mixed in a ratio of 1:1 as active materials, and then the active materials, conductive agent (90% conductive carbon black and 10% single-walled carbon nanotubes), styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed in a mass ratio of 97.5:0.5:2:0.5.
[0098] Example 4
[0099] The main difference between Example 4 and Example 1 lies in the first slurry, whose raw material ratio is as follows: first, graphite and silicon nanosheets are mixed in a ratio of 1:1 as active materials, and then the active materials, conductive carbon black, single-walled carbon nanotubes, styrene-butadiene rubber and sodium carboxymethyl cellulose are mixed in a mass ratio of 95:0.2:0.8:2:2.
[0100] Comparative Example 1
[0101] The main difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the first slurry and the second slurry are mixed in a ratio of 3:1 and then coated, and the thickness of the active layer formed by coating is 40 μm.
[0102] Comparative Example 2
[0103] The main difference between Comparative Example 2 and Example 1 is that Comparative Example 2 uses a flat copper foil with a thickness of 12 μm as the current collector instead of a porous copper foil.
[0104] Comparative Example 3
[0105] The main difference between Comparative Example 3 and Example 1 is that Comparative Example 3 uses silicon nanoparticles instead of the silicon nanosheets in Example 1.
[0106] Test: The negative electrode sheets prepared in the above-mentioned embodiments and comparative examples are prepared as follows to form lithium-ion batteries. Preparation of electrolyte: A mixed solvent of EC and DMC with a volume ratio of 1:1 is used to dissolve lithium hexafluorophosphate with a concentration of 1 mol / L to form an electrolyte. Preparation of half-cell: The negative electrode sheet is paired with the lithium sheet, and a three-layer film of PP / PE / PP is used as an isolation film to separate the negative electrode sheet and the lithium sheet, and the electrolyte is injected to form a button-type half-cell. The cut-off voltage is set to 0.01V~1.0V, and the rate is set to 0.2C. The batteries of the above-mentioned embodiments and comparative examples are cycled for 100 times of charge and discharge, and the first week reversible capacity, the 100th week reversible capacity, the cycle capacity retention rate and the volume expansion rate of the electrode sheet of each battery are tested. The results can be seen in Table 1.
[0107] Table 1
[0108]
[0109] As shown in Table 1, Example 1 uses a porous copper foil as a current collector, and sequentially forms a first active layer and a second active layer. The battery prepared in Example 1 has a significantly higher cycle capacity retention rate and a lower volume expansion rate, indicating that the strain of the composite negative electrode sheet as a whole during the charge and discharge process is relatively low, and the composite negative electrode sheet has a significantly higher cycle stability. Example 2 to Example 4 have similar structures to Example 1, and the main difference is only in the active materials used, which leads to differences in their first-week reversible capacities, but Example 2 to Example 4 also have significantly higher cycle capacity retention rates and lower volume expansion rates.
[0110] Compared with Example 1, Comparative Example 1 mixes and coats the first slurry and the second slurry. Among them, the cycle capacity retention rate of Comparative Example 1 is only 81.73%, which is significantly lower than the cycle capacity retention rate of Example 1, and the volume expansion rate of the pole piece of Comparative Example 1 is also significantly higher than that of Example 1. This shows that it is necessary to set a second active layer on the basis of the first active layer in order to effectively suppress the volume expansion of the first active layer. Comparative Example 2 uses a flat copper foil, and its cycle capacity retention rate is only 87.69%, and the volume expansion rate of the pole piece of Comparative Example 2 is also significantly higher than that of Example 1. This shows that the use of a porous copper foil with active material accommodating holes can effectively suppress the volume expansion of the first active layer. Comparative Example 3 uses silicon nanoparticles instead of silicon nanosheets, and its cycle capacity retention rate is only 73.54%, and the volume expansion rate is even higher. This is mainly because silicon nanoparticles can fill the active material accommodating holes. At this time, there is basically no vacancy in the active material accommodating holes for it to change volume. At this time, the second active layer alone is also difficult to suppress the expansion, pulverization and shedding of the first active layer.
[0111] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A composite negative electrode sheet, characterized in that: include: A current collector, the current collector having a plurality of active material containing holes opening on the surface of the current collector and having bottoms located in the current collector; a first active layer, wherein the active material in the first active layer includes a silicon active material, the silicon active material is in the form of nanosheets, the first active layer is disposed in contact with the surface of the current collector, and at least a portion of the silicon active material is located in the active material containing hole; and The second active layer comprises graphite, is disposed on a side of the first active layer away from the current collector, and entirely covers the first active layer.
2. The composite negative electrode sheet according to claim 1, characterized in that: The ratio of the thickness of the first active layer to the thickness of the second active layer is 1:(0.2-1.5).
3. The composite negative electrode sheet according to claim 1, characterized in that: The depth of the active material containing hole is 3 μm to 9 μm, and the overall thickness of the first active layer is 15 μm to 50 μm.
4. The composite negative electrode sheet according to claim 3, characterized in that: In the current collector, the diameter of the active material containing hole is 20 μm to 100 μm; and / or, The openings of all the active material containing holes on the surface of the current collector account for 30% to 80% of the surface of the current collector.
5. The composite negative electrode sheet according to any one of claims 1 to 4, characterized in that: In the first active layer, the thickness of the silicon active material is 5 nm to 100 nm; and / or, The radial size of the silicon active material is 100nm-2000nm.
6. The composite negative electrode sheet according to claim 5, characterized in that: The active material in the first active layer further comprises a carbon active material, wherein the carbon active material is selected from one or more of graphite, hard carbon, soft carbon and graphene, and in the first active layer, the mass ratio of the silicon active material to the carbon active material is 1:(0.5-2); and / or, The active material in the first active layer accounts for more than 80% by mass of the first active layer.
7. The composite negative electrode sheet according to claim 5, characterized in that: The first active layer further includes at least one of a first conductive agent and a first adhesive; wherein, The first conductive agent is selected from one or more of conductive carbon black, carbon nanotubes, graphene, carbon nanofibers and carbon-coated tin nanowires.
8. The composite negative electrode sheet according to any one of claims 1 to 4 and 6 to 7, characterized in that: The mass proportion of graphite in the second active layer is greater than 90%, and the second active layer further includes at least one of a second conductive agent and a second binder.
9. A battery, characterized in that: It comprises a negative electrode sheet, a positive electrode sheet and an electrolyte; the positive electrode sheet and the negative electrode sheet are arranged opposite to each other, and the negative electrode sheet is a composite negative electrode sheet as described in any one of claims 1 to 8.
10. An electrical device, characterized in that: It comprises an electric power consumption entity and the battery as claimed in claim 9, wherein the battery is used to supply power to the electric power consumption entity.
Citation Information
Patent Citations
Preparation method of negative pole piece and secondary battery
CN117410435A
Graphene-siloxene based composite anodes for lithium-ion batteries
IN202041036037A
Silicon anode materials for lithium ion secondary battery
KR102452519B1
Negative active material for rechargeable lithium battery and rechargeable lithium battery including the same
US20110206986A1